Snap without crackle or pop: a rude awakening. A case history of penile fracture. Issue 6 (1st November 2000) - Gilligan, P; Smith, M; Todd, F; Bradley, P; Shenton, A
Abstract : Penile fracture is a rare but worrying condition. The presentation to accident and emergency or primary care should not present difficulty in diagnosis but may cause concern with regard to initial treatment and definitive management. Emergency admission to a urologist is mandatory.